Letter to Jane Tolmach from Adolphus Reed - Adolphus Reed:::::: (1971)
In this January 8, 1971 letter, A. R. "Adolphous" Reed of the United Community Democratic Club sends Jane Tolmach a list of local "VIP" women he believes deserve to receive the Democratic Key in recognition of their campaign work. He expresses hope that they can be contacted and possibly honored at a meeting in San Diego, or that the keys be sent so he and Louise can distribute them. Reed thanks her for her assistance and notes he hopes to see her at the upcoming state meeting in Sacramento.